Comparative Analysis of Ventral Hernia Repair Techniques - Mittal, Vinamra; Ghildiyal, Divyanshu; Bindal, Vivek; Pandey, Dhananjay; Sachan, P.K; Mittal, Yamini (Medical Science: Trends and Innovations Vol. 10, 2025)
Background: Ventral hernia repair has evolved with the introduction of minimally invasive techniques, including laparoscopic and robotic-assisted approaches. This study compares open, laparoscopic, and robotic transabdominal pre-peritoneal (rTAPP) repair in terms of postoperative pain, recovery, hospital stay, complications, and cost-effectiveness. Methods: A comparative observational study was conducted over 12 months at two tertiary care hospitals. A total of 71 patients were analyzed for open vs. laparoscopic repair, while 111 patients (78 IPOM, 33 rTAPP) were compared for laparoscopic vs. robotic surgery. Data on demographics, pain scores, recovery time, complications, and costs were collected and analyzed. Results: Laparoscopic and robotic techniques significantly reduced post-operative pain, hospital stay, and return-to-work duration compared to open surgery. rTAPP had the lowest pain scores (VAS 0.36 at 1 month), shortest hospital stays (1.18 days), and fastest recovery. Open surgery had higher complication rates (7.04%) compared to laparoscopic (1.4%) and robotic (0%). However, robotic surgery incurred higher costs (INR 245,174.55 vs. INR 187,177.69 for IPOM). Conclusion: Minimally invasive techniques offer superior outcomes in ventral hernia repair. While robotic rTAPP provides enhanced precision, reduced pain, and faster recovery, its high cost remains a limitation. Future studies should assess long-term outcomes, recurrence rates, and cost-benefit balance to optimize surgical decision-making.